2018
DOI: 10.3389/fmed.2018.00285
|View full text |Cite
|
Sign up to set email alerts
|

Patient Involvement in the Lifecycle of Medicines According to Belgian Stakeholders: The Gap Between Theory and Practice

Abstract: Background: Patient involvement is often acknowledged as an important aspect of the lifecycle of medicines. Although different typologies exist, patient involvement has been described as the involvement of patients in decision-making regarding medicines. In view of the diversity of stakeholders and types of decisions in which patients might be involved, an in-depth understanding of these stakeholders' views toward involving patients in the lifecycle of medicines is essential.Methods: Interviews and surveys wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…EU regulation further requires clinical trial sponsors to provide summary results of their trials in a format understandable to laypersons, which may increase the opportunities for collaboration with patient representatives [13]. Patient involvement in the drug life cycle remains challenging, and gaps remain between theory and practice, as shown by a recent Belgian survey [34]. Involving patients and patient perspectives in the design of studies that include patient-reported outcomes is an important step [35].…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%
“…EU regulation further requires clinical trial sponsors to provide summary results of their trials in a format understandable to laypersons, which may increase the opportunities for collaboration with patient representatives [13]. Patient involvement in the drug life cycle remains challenging, and gaps remain between theory and practice, as shown by a recent Belgian survey [34]. Involving patients and patient perspectives in the design of studies that include patient-reported outcomes is an important step [35].…”
Section: Lessons Learned and Future Directionsmentioning
confidence: 99%
“…They are best positioned to provide a real-world understanding of their experiences and define their treatment preferences based on benefits and harms of treatment outcomes (1)(2)(3)(4)(5)(6)(7)(8)(9). As a result, an extensive trend toward making more patient-centric healthcare decisions has emerged, and experts have considered three possible levels of patient involvement referred to as micro, meso, and macro levels reliant on whether the involvement impacts patient-physician day-to-day interactions, a specific disease area, or resource allocation and healthcare policy decisions, respectively (10). While the role of patient with regard to microlevel decision, i.e., shared decision making, has significantly evolved in the last decades, when it comes to health authorities' decision making, the relative importance of patient voice remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In response to the growing interest of patient involvement, two trends, not mutually exclusive, have emerged: the first trend is "direct involvement" of patients in decision making, which is in favor of patients participating in discussions, such as through committees, advisory groups, or just testimonies, while the second trend is "indirect patient involvement" through studies allowing for the assessment of patient preferences (PPs) in a more systematic way (7,10,13). Moreover, researchers and policymakers have developed tools to assess PPs and initiated a variety of efforts and attempts to better include these PPs in benefit-risk assessment (BRA) and HTA decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Patient involvement is increasingly recognized as an integral part of healthcare and a critical component of safe and effective people-centered services. Engaged patients are more able to make informed decisions about their care options (1). Furthermore, resources may be better used if they are aligned with patients' priorities and this is critical for the sustainability of healthcare systems worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Patient-centered initiatives, such as the Innovative Medicines Initiative (IMI) have greatly added to the awareness that patients need to be at the center of a healthcare system. In order to participate in this innovation process, the European Patients' Academy on Therapeutic Innovation (EUPATI), a patient-led public-private partnership was created in 2012 (1). EUPATI aims to increase patient involvement by developing educational toolboxes and trainings.…”
Section: Introductionmentioning
confidence: 99%